Book Review of “Negotiating with the Devil Inside the World of Armed Conflict Mediation” Edited Pierre Hazan with the Collaboration of Emmanuelle Hazan - Kállai, Krisztina (Journal of Central and Eastern European African Studies, 2024)
.